Survival after Radical Prostatectomy versus Radiation Therapy in High-Risk and Very High-Risk Prostate Cancer - Chierigo, Francesco; Wenzel, Mike; Würnschimmel, Christoph; Flammia, Rocco Simone; Horlemann, Benedikt; Tian, Zhe; Saad, Fred; Chun, Felix K H; Graefen, Markus; Gallucci, Michele; Shariat, Shahrokh F; Mantica, Guglielmo; et al. (The Journal of urology, 2022)
PURPOSE: Our goal was to compare cancer-specific mortality (CSM) rates between radical prostatectomy (RP) vs external beam radiotherapy (EBRT) in National Comprehensive Cancer Network© (NCCN©) high risk (HR) patients, as well as in Johns Hopkins University (JH) HR and very high risk (VHR) subgroups. MATERIALS AND METHODS: Within the Surveillance, Epidemiology, and End Results database (2010-2016), we identified 24,407 NCCN HR patients, of whom 10,300 (42%) vs 14,107 (58%) patients qualified for JH HR vs VHR, respectively. Overall, 9,823 (40%) underwent RP vs 14,584 (60%) EBRT. Cumulative incidence plots and competing-risks regression addressed CSM after 1:1 propensity score matching (according to age, prostate specific antigen, clinical T and N stages, and biopsy Gleason score) between RP and EBRT patients. All analyses addressed the combined NCCN HR cohort, as well as in JH HR and JH VHR subgroups. RESULTS: In the combined NCCN HR cohort 5-year CSM rates were 2.3% for RP vs 4.1% for EBRT and yielded a multivariate hazard ratio of 0.68 (95% CI 0.54-0.86, p <0.001) favoring RP. In VHR patients 5-year CSM rates were 3.5% for RP vs 6.0% for EBRT, yielding a multivariate hazard ratio of 0.58 (95% CI 0.44-0.77, p <0.001) favoring RP. Conversely, in HR patients no significant difference was recorded between RP vs EBRT (HR 0.7, 95% CI 0.39-1.25, p=0.2). CONCLUSIONS: Our data suggest that RP holds a CSM advantage over EBRT in the combined NCCN HR cohort, and in its subgroup of JH VHR patients.
Keywords: senioři; analýza přežití; prostatektomie; prostata; Retrospective Studies; Survival Analysis; prostatectomy; program SEER; Neoplasm Grading; výsledek terapie; Risk Assessment; Middle Aged; mužské pohlaví; nádory prostaty; Kallikreins; prostatický specifický antigen; SEER Program; Prostate-Specific Antigen; věkové faktory; brachyterapie; kalikreiny; Neoplasm Staging; risk; hodnocení rizik; Prostatic Neoplasms; retrospektivní studie; Humans; radiotherapy; Prostatectomy; prostatic neoplasms; Propensity Score; Brachytherapy; lidé středního věku; stupeň nádoru; tendenční skóre; rizikové faktory; Age Factors; staging nádorů; Risk Factors; Aged; Treatment Outcome; Prostate; lidé; Male